Environmental risk assessment : a toxicological approach - Simon, Ted. (2014)
"Risk assessment is of increasing importance as health and safety regulations grow and become more complicated. Focusing on environmental risk assessment, this book looks at various factors relating to exposure and toxicity, human health, and risk. The book is aimed at practitioners and students who need to know more about understanding, developing, conducting, and interpreting risk assessments. It provides sufficient background to enable readers to probe for themselves the science underlying the key issues in environmental risk"--
Keywords: Environmental risk assessment; Environmental toxicology; MEDICAL / Public Health; MEDICAL / Toxicology; SCIENCE / Environmental Science